Tyrosine depletion attenuates dopamine function in healthy volunteers. - Harmer, C; McTavish, S; Clark, L; Goodwin, G; Cowen, P (2001)
RATIONALE: Tyrosine depletion has been shown to reduce dopamine over activity in animal and human investigations. However, the effects on basal dopamine function have not been explored. Such information could establish tyrosine depletion as an effective probe of dopamine function in healthy volunteers and would also have relevance for future therapeutic applications of this manipulation. OBJECTIVE: The present study investigated the effect of acute tyrosine depletion on dopamine function in healthy volunteers using a combination of neuroendocrine, neuropsychological and subjective measures. METHODS: On one occasion, volunteers received an amino acid drink selectively lacking tyrosine and phenylalanine (TYR-free), whilst on the other they received a balanced (BAL) amino acid drink. Plasma prolactin, amino acid levels and subjective state were monitored over 6 h following the two drinks, and volunteers also completed a battery of tests from the CANTAB, including measures of spatial memory previously found to be sensitive to changes in dopamine function. RESULTS: Plasma prolactin levels rose following the TYR-free drink relative to the balanced mixture, indicative of decreased dopamine neurotransmission within the hypothalamus. Following the TYR-free drink, volunteers were impaired at spatial recognition memory and spatial working memory. Volunteers also tended to report that they felt less good following the TYR-free than the BAL mixture. CONCLUSION: Tyrosine depletion in healthy volunteers affected baseline dopamine function on the different measures employed in this study. Tyrosine depletion would thereby seem valuable as a probe of dopamine function in human volunteers. Ratings of depression and other aspects of cognitive function were unaffected, suggesting that this manipulation may be free of significant side effects when used as a treatment for conditions characterised by dopamine over activity, such as acute mania and schizophrenia.